ANALISIS PENERIMAAN PENGGUNA SP4N–LAPOR! DI DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI SULAWESI TENGAH MENGGUNAKAN METODE (TAM) - Natalia Warani; Deny Wiria Nugraha (LPPM Universitas Abdurrab, 2026)
SP4N-LAPOR Public Complaint System! It is an important medium to convey people's complaints and aspirations to the government digitally. To ensure the impact of the ease of use and usefulness of the system on the intention to use the service, it is still necessary to assess the level of acceptance of the system's users. This study used a (TAM) approach to test the acceptance of SP4N-LAPOR! users. Questionnaires were distributed to SP4N-LAPOR! users in Central Sulawesi Province to collect research data. Validity tests, reliability tests, descriptive analysis, and simple linear regression are used in the analysis. With a contribution of the determination coefficient value (R²) of 20.2%, the findings show that the Perception of Ease of Use (PEOU) has a positive and significant influence on the Perception of Usefulness (PU). Furthermore, the perception of usefulness (PU) had a positive influence on behavioral intention (BI) 39.3% and the perception of ease of use (PEOU) had a positive influence on behavioral intention (BI) 26.7%. These findings show that user acceptance of SP4N-LAPOR! It is greatly influenced by the ease of use and usefulness of the system.